Infectious Scleritis: Pathophysiology, Diagnosis, and Management. Issue 8 (August 2021) - Yu, Julia; Syed, Zeba A.; Rapuano, Christopher J.
Abstract : Abstract: Infectious scleritis (IS) is a rare and severe ocular disorder responsible for approximately 5%–15% of all scleritis cases. It is often associated with a poor prognosis due to its similar clinical presentation to autoimmune scleritis, resulting in a delayed diagnosis and treatment. Therefore, differentiating between infectious and noninfectious entities is critical. Several details extracted from the patient's history and clinical examination can raise suspicion for infection. The most common predisposing factor is previous ocular surgery, especially pterygium, cataract, and vitreoretinal surgeries. Ocular trauma, poor contact lens hygiene, "eye-whitening" procedures, and subtenon triamcinolone injections have also been implicated. Clinical features of infection include the presence of scleral necrosis, hypopyon, unifocal or multifocal scleral abscesses, and mucopurulent discharge. Thorough diagnostic testing is essential before excluding infection as a possibility. Empiric broad-spectrum topical and systemic antibiotic therapy should be initiated while awaiting laboratory results and adjusted accordingly. Most IS cases require both aggressive medical and surgical treatment, and various studies have reported favorable outcomes with this combination. At this time, there is no consensus on the management of this severe ocular condition, and future studies are needed to establish clear treatment guidelines.